2017
DOI: 10.1007/s10072-017-3075-6
|View full text |Cite
|
Sign up to set email alerts
|

Affective symptoms and determinants of health-related quality of life in Mexican people with epilepsy

Abstract: Epilepsy is known to be associated with multiple psychiatric comorbidities, such as depression, sleep-disorders, and anxiety. The objective of this study was to determine the prevalence and impact of affective symptoms over health-related quality of life (QOL) in Mexican people with epilepsy (PWE). We performed a cross-sectional observational study on 73 consecutive PWE and corresponding age- and sex-matched controls. HrQOL was assessed using the QOLIE-10 (QOL in Epilepsy-10) instrument. Clinical and demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…Furthermore, the adverse effects of AEDs play a major negative role in QoL modulation [14,45,54,55]. The strong association between the presence of depression and the QoL in patients with epilepsy has already been established [12,13,16,42,44,45,56]. Previous studies have indicated that psychological factors, especially depression were more important predictors of a patients' quality of life, compared to epilepsy characteristics [30,31,57].…”
Section: Quality Of Lifementioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the adverse effects of AEDs play a major negative role in QoL modulation [14,45,54,55]. The strong association between the presence of depression and the QoL in patients with epilepsy has already been established [12,13,16,42,44,45,56]. Previous studies have indicated that psychological factors, especially depression were more important predictors of a patients' quality of life, compared to epilepsy characteristics [30,31,57].…”
Section: Quality Of Lifementioning
confidence: 99%
“…With regards to epilepsy characteristics, the duration of epilepsy has been reported to be both related [51] and unrelated [12] to quality of life. However, it is widely accepted that seizure frequency considerably affects patients' QoL [31,41,52,53], as long as polypharmacy has been found to be associated with poorer QoL [13,16,52,53]. Furthermore, the adverse effects of AEDs play a major negative role in QoL modulation [14,45,54,55].…”
Section: Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…45 El segundo publicado en 2005 mostró una calificación promedio de QOLIE-31 para los PCE de 55 puntos y detectó que los trastornos del sueño, un estado socioeconómico bajo, el género femenino y un mal control de crisis se asociaron a reducción de la CV. 46 Otro estudio en población mexicana de PCE adultos de casos y controles reveló una relación en pérdida de CV por QOLIE-31 y la presencia de depresión/ansiedad, y mala calidad de sueño 47 acentuado por el conocimiento previo de prevalencias altas de trastornos de ansiedad y depresión (hasta 25%) en PCE adultos mexicanos. 48 La CV también se ve afectada en los cuidadores de PCE mexicanos, lo cual fue demostrado en un estudio realizado en un centro hospitalario de tercer nivel, donde se encontró un nivel de desgaste (ND) moderado en los cuidadores y una calidad de vida con puntajes de 47-55 en la escala WHOQOL-BREF (puntuación de 0 a 100, con peor CV con menor puntaje).…”
Section: Wwwmedigraphicorgmxunclassified